Why Must the Ukrainian War Have Happened? How Did the West Ignore the Signs of Impending Tragedy? - Stanislawski, Jacek (Narzędzia wojny, 2023)
The article is going to reflect on the variety of origins leading to the current armed conflict in Ukraine. It will adopt the interdisciplinary approach, mainly sociological, political, and historical. Thus, instead of focusing on one important issue, I will try to gather the collective cause of the ongoing tragedy. The elaboration will analyse the recent history of the relations between Russia and the Western countries, and try to place the role of Ukraine in it. The main errors regarding the foreign policies of the West, as well as those regarding the Euro-Atlantic integration will be pointed out, too. The other issues that the Western world is facing will not remain unmentioned. It will be demonstrated what could have been done, so that the conflict never broke out. The assessment of the current circumstances will provide suggestions what the countries should do to avoid any similar dramatic scenario in the future. Finally, I will consider several possible outcomes of the present situation. Apart from describing the pure facts available in the literature, I will share with my own experiences in the West, in Russia, and in Ukraine. I will stress how the phenomenon of propaganda is affecting the population. I will try to combine the general knowledge with the perception of the facts by ordinary people.